Design, synthesis, biological evaluation and molecular docking study of 2,4-diarylimidazoles and 2,4-bis(benzyloxy)-5-arylpyrimidines as novel HSP90 N-terminal inhibitors - Man Yang; Chenyao Li; Yajing Li; Chen Cheng; Meiyun Shi; Lei Yin; Hongyu Xue; Yajun Liu (Journal of Enzyme Inhibition and Medicinal Chemistry)
The molecular chaperone HSP90 plays an essential role in cancer occurrence and development. Therefore, it is an important target for the development of anticancer drugs. 1,3-Dibenzyl-2-aryl imidazolidine (8) is a previously reported inhibitor of HSP90; however, its anticancer activity is poor. In this work, chemical modification of 8 led to the discovery of 2,4-diarylimidazoles and 2,4-bis(benzyloxy)-5-arylpyrimidines as two types of novel HSP90 N-terminal inhibitors. 16l and 22k exhibited antiproliferative activity against multiple breast cancer cell lines with IC50 values at the low micromolar level. 16l and 22k induced significant degradation of the client proteins AKT and ERK and a lower level of the heat shock response in comparison with tanespimycin (17-AAG). 22k exhibited a strong affinity for the HSP90α N-terminus with an IC50 value of 0.21 μM. A molecular docking study revealed that 16l and 22k successfully bind to the geldanamycin binding site at the N-terminus of HSP90α.